Analisis Peluang, Ancaman, dan Strategi Penjualan Melalui Aplikasi Tiktok Shop dan Tokopedia di Wilayah Tangerang - Vera Maria; Ivanka Putri Kamaliya; Karina Widya Mareta; Latifah Rahwawati; Najwa Widodo Putri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze oppurtunities, threats, and sales strategies through the Tiktok Shop and Tokopedua applications in the Tangerang area. Tiktok Shop and Tokopedia are two major E-Commerce platforms in Indonesia. Tiktok Shop utilizies short video trends and live streaming features to attract young consumers, while Tokopedia offers a strong E-Commerce infrastructure to support online transactions. E-Commerce is a process whereby buyers and sellers exchange information, money, and goods using electronic media. Data collection techniques were carried out through surveys targeting the community in the Tangerang area by distributing questionnaires and using documentation and literature studies that compiled secondary data from official documents published by the Ministry of Cooperatives and Small and Medium Enterprises, APJII, Data Reportal, and the Tangerang City Communication and Information Agency. The result of this study show that the collaboration between Tiktok Shop and Tokopedia opens up enormous growth opportunities, especially for businesses in the Tangerang area. Tangerang is a region with rapid growth in internet users. The younger generation, who actively use tiktok for both entertainment and shopping, is a highly potential consumer segment. Through this collaboration, businesses can reach markets that were previously difficult to penetrate through traditional marketing methods.